The scandal of continuity in Middle East anthropology form, duration, difference - Scheele, Judith 1978-; Shryock, Andrew 1963- (Indiana University Press, 2019)
Despite a rich history of ethnographic research in Middle Eastern societies, the region is frequently portrayed as marginal to anthropology. The contributors to this volume reject this view and show how the Middle East is in fact vital to the discipline
Keywords: Ethnologie; Naher Osten; Südasien; Anthropology / Middle East; Ethnology / Middle East; Anthropology; Ethnology; Middle East; Aufsatzsammlung